(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
In this interview, carried out at the Künstlerhaus Mousonturm theatre in Frankfurt in February 2019, Helgard Haug, director of Rimini Protokoll, states her critical and theoretical positioning towards theatre. Among observations of her artistic reasons and creation processes, she particularly comments on DO’s & DON’Ts - Eine Fahrt nach allen Regeln der Stadt (2018), Situation Rooms (2013), Welt-Klimakonferenz (2014) e Weltzustand Davos (Staat 4) (2018).